2014
DOI: 10.1659/mrd-journal-d-13-00030.1
|View full text |Cite
|
Sign up to set email alerts
|

Ecological Factors Influencing Physical Soil Degradation in the Atacora Mountain Chain in Benin, West Africa

Abstract: This study analyzed the ecological factors influencing soil degradation in the Atacora Mountains in northern Benin, which harbor two endemic species, Thunbergia atacorensis and Ipomoea beninensis. Data were collected along line transects from plain to summit within 22 plots of 30 m 3 30 m. Indicators of physical soil degradation (extent of organic layer, color of topsoil, compactness of soil, presence and extent of rills, and occurrence of sheet erosion) and environmental factors (canopy and ground cover, topo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 29 publications
(38 reference statements)
1
4
0
Order By: Relevance
“…Cultivated area that is generally located in the middle and lower places, however, did not show the same trend (Figure 1). This result seems to be similar with the result of Okou et al (2014) who found that high slope angles in high elevation often result in lightly degraded soil. This condition is allegedly due to the effect of high dense of canopy cover in protected forest that decreases kinetic power of rainfall that will damage the soil through soil erosion process.…”
Section: Degraded Land and Biophysical Factorssupporting
confidence: 91%
“…Cultivated area that is generally located in the middle and lower places, however, did not show the same trend (Figure 1). This result seems to be similar with the result of Okou et al (2014) who found that high slope angles in high elevation often result in lightly degraded soil. This condition is allegedly due to the effect of high dense of canopy cover in protected forest that decreases kinetic power of rainfall that will damage the soil through soil erosion process.…”
Section: Degraded Land and Biophysical Factorssupporting
confidence: 91%
“…In these areas, the study area has a low risk of erosion on surfaces with high slope coverage. According to Okou et al (2014) higher slope can also provide a natural protection against soil erosion. In higher elevation areas with more sensitive ecosystems such as grassland and rock outcrops, erosion-sensitive areas depend on soil status, slope, and type of land cover (Stanchi et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of physical soil degradation indicators (extent of organic layer, color of topsoil, compactness of soil, presence and extent of rills, and occurrence of sheet erosion) each plot was classified visually into specific soil degradation classes. Physical soil degradation in the study area falls into four grades, namely light, moderate, high and extreme soil degradation classes described in [23]. The characteristics of each class are summarized in Table 1.…”
Section: Sampling Data and Classification Of Plots Into Soil Degradatmentioning
confidence: 99%
“…This finding could be explained by the fact that the soil aggregate stability is closely related to soil organic matter composition [35], biological activity [36], infiltration capacity [37], water absorption and retention in the biomass and upper rhizosphere [38,39] and erosion resistance [37]. Physical soil degradation on the hillsides of Atacora mountain was characterized by the removal of the organic layer and the modification of soil structure leading to the occurrence of ferricrete (extremely degraded soils) [23]. Soil degradation had resulted in soil loss, nutrient depletion, changes in soil structure, and soil hardening that limited plant root system penetration.…”
Section: Impacts Of Soil Degradation On Phytodiversitymentioning
confidence: 99%
See 1 more Smart Citation